Character education based on the value sand norms of the Indonesian philosophical system - Yulius Rustan Effendi (Sophía: Colección de Filosofía de la Educación)
The purpose of this article is to elucidate how the principles of nationalism influence students' attitudes and behaviors, shaped by the norms and values of Pancasila, a philosophical system. The methodology employed for data collection involves a systematic review (meta-synthesis) of digital sources, encompassing an analysis of meta-ethnographic studies. The meta-ethnographic model serves as an "interpretive" tool, facilitating a comprehensive exploration of pivotal studies and their connection to the concept of character education in nationalism within the Pancasila framework. In order to delve into the realm of interpretive studies, there is a need to acquire "iterative" (spiral) data, deconstructing the ontological, epistemological, and axiological dimensions of the Pancasila philosophy. Employing this interpretive approach, the author chronicles the progress in the implementation of character education focused on nurturing students' sense of nationalism. This approach is rooted in the values and appreciation of the norms encapsulated in Pancasila, which, up until now, have not been fully optimized within the school context. Furthermore, the authors expand upon the foundational study, meticulously analyzing the concept of Pancasila within an intricate web of philosophical interpretations. This intricate analysis aims to decipher the essence of existence that students should embrace in their lives.